A Survey on Blockchain Technology- Taxonomy, Consensus Algorithms and Applications - Tinu, NS (International Journal of Computer Sciences and Engineering, 2025)
Blockchain is a buzzword in the current technology trends. It is usually coupled with the cryptocurrency terms: Bitcoin and Ethereum. Any applications that can be optimized by decentralization and that needs to be highly secured could opt for this technology. Blockchain technology has already entrenched into the finance and banking domains by its unusual transparency, security, and flexibility, that facilitates the control of transactions in a decentralized manner. Its distributed and peer-authentication features empower it to span across auxiliary domains like Contractual Agreements and Real Property, Smart Grids, Gaming and Entertainment, Government public services and Smart Cities with IOT, reputation systems, and security services. This paper provides a description of key characteristics, architecture, and taxonomy of blockchain technology. Moreover, the paper provides an insight into the popular consensus algorithms, technical challenges, and major application areas. Future trends and signs of progress in the blockchain technology were discussed.